Maternal and cord blood zinc (Zn), IGF-1, IGFBP3 levels in IUGR neonates - (:unkn) unknown (MEDIMOND PUBLISHING CO, 2005)
The aim of this study was to determine the relationship between maternal serum Zn levels and birth weight of the offspring and correlation of these with cord blood Zn, IGF-1 and insulin-like growth factor binding protein 3 (IGFBP3) levels. 22 term small-for-gestational-age (SGA) and 34 term appropriate-for-gestational -age (AGA) babies and their mothers have been evaluated. There was no significant difference between the IGF-1 and IGFBP-3 levels and birthweight of the babies of the mothers with and without Zn deficiency. A correlation was found between the birthweight, IGF-1 and IGFBP-3 levels, BMI of the mother and weight gain of the mother during pregnancy (p<0.01).
Keywords: GROWTH-FACTORS